MASYARAKAT AGAMA HINDUISME DAN BUDDHAISME (KAJIAN SOSIOLOGI AGAMA) - Aeni, Nurul (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2021)
This article examines Hinduism and Buddhism in the study of the sociology of religion. the concept of religion in the reality of people's lives is often a trigger for conflict due to not understanding one another. So to eradicate religious conflict in a society that claims the truth, it is important to discuss it in the realm of the sociology of religion. Because the sociology of religion plays a role in this. So the purpose of this article is to know how to understand religion in Hinduism, Buddhism and what kind of religious teachings are contained in it. The results of this study indicate that the sociology of religion is able to contribute through the public's perspective on one religion to another. So as to be able to build a harmonious and prosperous life in community life.